Morphology of the male reproductive system of freshwater prawn Macrobrachium carcinus (Decapoda, Caridea): Functional and comparative aspects - Ruiz, Thalles F. R. [UNESP]; Vidal, Mateus R. [UNESP]; Gardinal, Mario V. Buzete [UNESP]; Ribeiro, Karina; Vicentini, Carlos A. [UNESP]; Franceschini Vicentini, Irene B. [UNESP] (Wiley, 2020)
Testes and vasa deferentia are parts of the male reproductive system of decapod crustaceans. Both organs show morphological differences among decapod species in terms of anatomical and histological patterns reflecting the diversity of this group. Describing these features may assist in systematics, phylogenetics, and studies of reproductive behavior, especially for species of commercial interest, such as Macrobrachium carcinus, a native American species that, unusually for this genus, has no precopulation courting behavior. This study aims to describe the reproductive morphology and spermatogenesis of the male freshwater prawn M. carcinus. The male reproductive system of this species consisted of lobed testes connected to the vasa deferentia. The testis of M. carcinus was divided into several lobules. Each lobule was formed by a cluster of germ cells surrounded by connective tissue and nurse cells. This microscopic anatomy and histology of the testicular histoarchitecture has been described for many species of Decapoda and may represent a derived design of the testes. Unlike that in other decapod species, spermatogenesis proceeds in short transitory phases that produce spermatozoa at high concentrations and frequencies, corroborating the uncommon male reproductive behavior of this species. In the spermatic pathway, the lobules develop and fuse before releasing spermatozoa from the testes; however, this process has not been observed in decapods, yet. The neutral compounds secreted by the vas deferens are important for sperm nutrition as females secrete a substance for spermatophore adhesion during reproduction. This study presents different features and dynamics of the spermatogenic process in the male reproductive system of M. carcinus that have not yet been presented in the literature for decapods.
Keywords: reproduction; spermatic pathway; spermatogenesis; spermatozoa; testes